Content of Orthopedic Patient Education Provided by Nurses in Seven European Countries - Charalambous, Andreas; Papastavrou, Evridiki; Valkeapää, Kirsi; Zabalegui, Adelaida; Ingadottir, Brynja; Lemonidou, Chryssoula; Fatkulina, Natalja; Jonko, Katajisto; Leino-Kilpi, Helena (My University, 2018)
Patients' and their significant others' education during the perioperative phase is an important and challenging aspect of care. This study explored the content of education provided by nurses to arthroplasty patients and their significant others. Data were collected with the Education of Patients-NURSE content (EPNURSE-Content), Received Knowledge of Hospital Patient (RKhp), and Received Knowledge of Significant Other (RKso) scales. The results showed that the content of education emphasized biophysiological and functional needs, differed between countries, and was related to how physically demanding nurses found their job to be and the amount of education provided. There is congruence between the received knowledge of patients and their significant others in relation to the content of education provided by nurses. The findings can support nurses in developing aid material for patients and significant others explaining the nature of education and advising them what to expect and how to optimize their participation in the process.
Keywords: Adult nursing; Knowledge; Orthopedics; Patient education; Quantitative methods